The Role of Administrative Bodies in the Syistem of Democratic Control of Modern Armed Forces, With Emphasis on the Armed Forces of Bosnia and Hercegovina - Hodžić, Eldin; Musa, Rusmir (Uprava, 2025)
The foundations of the modern understanding of democratic control of the armed forces have been the subject of many scientific works in the past period. This refers primarily to the accentuation of general assumptions for the establishment of democratic control of the armed forces, the past experiences related to the present limitations in the social segment in question, the perspectives and further direction of development, and the specific role of state administrative bodies during the implementation and establishment of elements of democratic control of the state security system in general. The basis of the complete elaboration in this scientific work is on the general characteristics of the position and functioning of the armed forces in modern democratic systems and the established mechanisms of democratic control of the Armed forces of Bosnia and Herzegovina within the framework of the Dayton Peace Agreement, more specifically its Article IV (Constitution of BiH).